Designing an annual training plan for a young developing squash player: A case study - Gamble, P. (Journal of Australian Strength and Conditioning, 2013)
In this article an annual plan is detailed for a young developing male squash player making the transition from junior competition to the senior professional world tour and Professional Squash Association (PSA) circuit. Each of the programme goals are discussed with reference to the relevant literature from squash and other racquet sports. This information is also presented in the context of the demands of squash at elite level. The specific training methods employed in order to meet these challenges and address the various programme goals outlined are described. Finally, aspects of planning and scheduling are discussed and examples of how different training approaches are integrated throughout the training year and within each training cycle are provided.